AKTIVASI KEMBALI LIMBAH ARANG AKTIY DARI PABRIK GULA KETELA POHON - Gustan Pari; Hartoyo Hartoyo (Pusat Penelitian dan Pengembangan Hasil Hutan, 1989)
A re-activation study of activated charcoal residue from glucose factory has been undertaken at the FPRDC in Bogor, and the result presented in this paper. The residue was subjected to three different treatments, namely unwashed, and washed with respectively 1 % HCl solution and water. Following the treatment, each residue material was then heated in an el.ectric retort, using four different temperatures : 600, 700, 800, and 900°C for 25 minutes. The response evaluated of activated charcoal are the yield, benzene and iodine adsorption. Bleaching test of sugar was then conducted, and the result compared with that obtained using commercial activated carbon.The result shows that heating temperature of 700, 800, and 900°C gives iodine adsorption value, will above 500 mg/g activated carbon. The benzene adsorption value on the other hand is below 39 percent. The bleaching ability of reactivated charcoal on sugar is similar to that of commercial activated carbon.